2007
DOI: 10.1021/jp072792q
|View full text |Cite
|
Sign up to set email alerts
|

Wax Inhibition by Comb-like Polymers:  Support of the Incorporation−Perturbation Mechanism from Molecular Dynamics Simulations

Abstract: Deposition of wax on a cold surface is a serious problem in oil production. Progress in developing more effective wax inhibitors has been impeded by the lack of an established mechanism connecting the molecular structure to inhibitor efficiency. Some comb-like polymers having long alkyl side chains are known to decrease the rate of wax formation. Among several possible mechanisms, we investigate here the incorporationperturbation mechanism. According to this mechanism, the inhibitor molecules in oil are prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 40 publications
0
71
0
Order By: Relevance
“…It has been reported that comb‐shaped inhibitors are known to be more effective compared to linear inhibitors . The comb‐shaped inhibitor (oligomer of poly [octadecyl acrylate]) reduces the cohesive energy density (driving force for ordering transformation) three times compared to no inhibitor . The linear inhibitor can self‐assemble into micelle‐like aggregates providing a crystalline form and soluble hairy platelet structures that surround the core, and these structures can reduce the super‐saturation, delay the growth rate of wax crystals, and form abundant smaller wax crystals .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that comb‐shaped inhibitors are known to be more effective compared to linear inhibitors . The comb‐shaped inhibitor (oligomer of poly [octadecyl acrylate]) reduces the cohesive energy density (driving force for ordering transformation) three times compared to no inhibitor . The linear inhibitor can self‐assemble into micelle‐like aggregates providing a crystalline form and soluble hairy platelet structures that surround the core, and these structures can reduce the super‐saturation, delay the growth rate of wax crystals, and form abundant smaller wax crystals .…”
Section: Resultsmentioning
confidence: 99%
“…Even though many studies were reported in the literature, the exact mechanism of wax inhibitors is still not completely understood. Several mechanisms including the incorporation‐perturbation theory, nucleation sequestering theory, and adsorption on pipe wall theory have been proposed. The nucleation sequestering theory suggested that the wax inhibitor can affect the nucleation process.…”
Section: Introductionmentioning
confidence: 99%
“…To help prevent the nucleation and formation of wax crystals, wax inhibitors are typically used during crude oil production. Wax inhibitors are generally comb polymers, ethylene polymers, and copolymers, and other branched polymers with long alkyl chains (Jang et al 2007;Kelland 2009). These polymers contain a segment capable of solubilizing wax molecules and a segment that interferes with the packing of wax molecules to form crystals.…”
Section: Statement Of Hypothesismentioning
confidence: 99%
“…Other work have successfully studied the interaction between crystal planes of wax and EVA in diesel fuels had been made by Wu et al and Zhang et [17], [18]. In addition, the mechanism of wax inhibition was successfully been studied by Jang et al (2007) where their focussing on incorporation-perturbation mechanism. This mechanism investigation included the enthalphic aspect of the molecular level interaction between a wax and inhibitor in crude oil [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mechanism of wax inhibition was successfully been studied by Jang et al (2007) where their focussing on incorporation-perturbation mechanism. This mechanism investigation included the enthalphic aspect of the molecular level interaction between a wax and inhibitor in crude oil [2]. Behind to this mechanism, the inhibitor molecules in oil are preferentially partitioned (incorporation) toward the wax-rich (amorphous) wax deposits (soft wax), which then serves as a perturbation to slow down the ordering transition of soft amorphous wax into more stable but problematic hard wax crystals.…”
Section: Introductionmentioning
confidence: 99%